A high performance three-dimensional thiophene-annulated perylene dye as an acceptor for organic solar cells. Issue 77 (5th September 2016) - Fan, Wei; Liang, Ningning; Meng, Dong; Feng, Jiajing; Li, Yan; Hou, Jianhui; Wang, Zhaohui
Abstract : A new three-dimensional thiophene-annulated perylene dye, namely tetra-PBI-S, was designed and synthesized. Organic solar cells based on the tetra-PBI-S acceptor show a much higher power conversion efficiency than tetra-PBI based solar cells. Abstract : A high performance three-dimensional (3D) thiophene-annulated perylene dye, namely tetra-PBI-S, was designed and synthesized. The appropriate LUMO level, balanced carrier mobilities and favourable phase separation make tetra-PBI-S based solar cells show a much higher power conversion efficiency (PCE) of 6.2% than tetra-PBI based solar cells with a PCE of 3.6%.